Juventude e risco: problematizando os sentidos construídos por jovens sobre esta relação - Pontes, Alexandre Kerr (2011)
In contemporary youth research, risk has become not only a concept, but a paradigm. This statement was explored in this research through the concept of biopolitics, which can give us a better understanding of how this came to be. Therefore, in search of a different perspective on the studies of risk and youth, this research tries to call upon another logic of comprehension to understand the meaning of risk behavior. To do this, interviews were used to understand how young people give meaning to risk. The methodology was based in Mary J. Spink conception of practices of discourse and production of meaning. Even though a rupture to normative thought in risk meaning was sought, the discourses of the interviewed showed that, not only they incorporated the normative meaning of risk, but that even when there was a rupture with risk paradigm, they would find themselves entangled in a web of other normative logics.